KAJIAN JEJAK KARBON (CARBON FOOTPRINT) DI FMIPA UNIVERSITAS NEGERI SEMARANG - Rahayuningsih, Margareta -; Handayani, L.; Abdullah, M.; Solichin, Solichin; Arifin, M.S. (Indonesian Journal of Conservation, 2021)
Human activities that produce carbon dioxide emissions and are called carbon footprints or carbon footprints have a big role in global warming. As part of its contribution to climate change mitigation efforts and environmental preservation, Faculty of Mathematics and Natural Science Universitas Negeri Semarang (FMIPA UNNES) has been actively developing conservation policies. The programs developed as an effort to mitigate climate change have been running for a long time. However, so far it is not certain how much CO2 emissions are produced and minimized by FMIPA UNNES. The purpose of this study was to analyze the amount of CO2 emissions produced in the FMIPA environment, to map the carbon footprint (CO2) produced from activities on the Unnes campus, to identify what factors influence CO2 emissions resulting from activities in FMIPA. The research was conducted from May to October 2020. The data obtained were obtained from primary data and secondary data. Primary data were obtained through field surveys, while secondary data were obtained from existing data. The carbon footprint that will be taken is obtained from electronic measurements, waste and transportation. The data instrument was converted into carbon footprint units (grams CO2-ek) using a carbon footprint calculator (Ver 2) developed by IESR. The results showed that the carbon footprint generated from campus activities at FMIPA in 2020 before the Covid-19 pandemic outbreak was 10,670.25 ton CO2-eq / month. This carbon footprint decreased during the pandemic to 4,312.27 ton CO2-eq / month. This total carbon footprint consists of scope one in the form of transportation activities by operational vehicles and use of LPG, scope two of electricity spending activities, scope three in the form of transportation activities by lecturers, staff, and students, use of paper, and waste disposal.